Implementasi Jaringan 4G Pada Layanan Video Conference - Sofinanda Sari; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Video conferencing is a long-distance interactive communication service that can bring together two or more people using broadband internet services. This service can send and receive data in the form of audio and video simultaneously or two-way transmission techniques. Data in the form of audio and video, which have a large enough bandwidth, require a network capable of meeting bandwidth requirements. Observations were made for 12 days in the Pekanbaru area, Panam. The results of this study have concluded that the superior throughput is Telkomsel with a data size of 1003429.76 ms. This is evidenced by the quality offered and the clarity of the image during the video conference. Keywords: H.264 Codec, LTE, Multipoint, QOS, Video Conference.